Sensory Profile and Consumer Preference Analysis of Robusta and Arabica Coffee with Ginger and Lemongrass Addition - Rizkia Ayu Shafaningrum; Jariyah; Yunita Satya Pratiwi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Consumer-based sensory profile assessment of the use of spices in coffee beverages is necessary to determine consumer acceptance. This study aims to describe the sensory profile and analyse the relationship between the sensory profile and consumer preferences for robusta and arabica ground coffee with the addition of ginger and lemongrass at various concentrations. The sensory profile was determined using the rate-all-that-apply (RATA) method, resulting in 22 attributes covering the sensory attributes of robusta and arabica coffee with the addition of ginger and lemongrass, namely sweet aroma, sour aroma, bitter aroma, roasted aroma, nutty aroma, cocoa aroma, spicy aroma, sour taste, bitter taste, roasted taste, burnt taste, nutty flavor, cocoa flavor, gingery flavor, lemongrass flavor, mouthfeel body, mouthfeel rough, mouthfeel mouth drying, mouthfeel burnt, aftertaste bitter, aftertaste sour, and aftertaste spicy. The panellists' preference mapping showed that 60%–80% of panellists had above-average preference scores for sample K1 625, a robusta coffee treatment with the addition of 5% ginger and 5% lemongrass, with a dominant bitter aroma. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero hungerSDG 8: Decent work and economic growthSDG 9: Industry, innovation, and infrastructure